Spatial and Functional Aspects of ER-Golgi Rabs and Tethers - Saraste, Jaakko (Frontiers in Cell and Developmental Biology, 2016)
Two conserved Rab GTPases, Rab1 and Rab2, play important roles in biosynthetic-secretory trafficking between the endoplasmic reticulum (ER) and the Golgi apparatus in mammalian cells. Both are expressed as two isoforms that regulate anterograde transport via the intermediate compartment (IC) to the Golgi, but are also required for transport in the retrograde direction. Moreover, Rab1 has been implicated in the formation of autophagosomes. Rab1 and Rab2 have numerous effectors or partners that function in membrane tethering, but also have other roles. These include the coiled-coil proteins p115, GM130, giantin, golgin-84, and GMAP-210, as well as the multisubunit COG (conserved oligomeric Golgi) and TRAPP (transport protein particle) tethering complexes. TRAPP also acts as the GTP exchange factor (GEF) in the activation of Rab1. According to the traditional view of the IC elements as motile, transient structures, the functions of the Rabs could take place at the two ends of the ER-Golgi itinerary, i.e., at ER exit sites (ERES) and/or cis-Golgi. However, there is considerable evidence for their specific association with the IC, including its recently identified pericentrosomal domain (pcIC), where many of the effectors turn out to be present, thus being able to exert their functions at the pre-Golgi level. The IC localization of these proteins is of particular interest based on the imaging of Rab1 dynamics, indicating that the IC is a stable organelle that bidirectionally communicates with the ER and Golgi, and is functionally linked to the endosomal system via the pcIC.